2020
DOI: 10.3390/ijerph17239063
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Mitigation Policies and Co-Impacts on Indigenous Health: A Scoping Review

Abstract: Climate change mitigation policies can either facilitate or hinder progress towards health equity, and can have particular implications for Indigenous health. We sought to summarize current knowledge about the potential impacts (co-benefits and co-harms) of climate mitigation policies and interventions on Indigenous health. Using a Kaupapa Māori theoretical positioning, we adapted a validated search strategy to identify studies for this scoping review. Our review included empirical and modeling studies that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
(173 reference statements)
1
20
0
1
Order By: Relevance
“…Thus, the design and implementation of specific policies within the pathways is fundamental to achieving any reduction in inequities. 39 This is likely to pose a significant challenge to the transport sector, which has only just started to think about equity in planning and policy. 40 Moreover in Aotearoa, the transport sector has, until relatively recently, actively pursued policies that discriminate against Māori.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the design and implementation of specific policies within the pathways is fundamental to achieving any reduction in inequities. 39 This is likely to pose a significant challenge to the transport sector, which has only just started to think about equity in planning and policy. 40 Moreover in Aotearoa, the transport sector has, until relatively recently, actively pursued policies that discriminate against Māori.…”
Section: Discussionmentioning
confidence: 99%
“…In this instance we are interested in transferability to health policies and institutional responsiveness to climate change for Māori, with a focus on structural elements and systems change. Despite the absence of publications that focus on Indigenous and Māori vulnerabilities (Jones et al, 2020), climate change is an area in which Indigenous people are severely at risk. In undertaking our analysis, we took an iterative thematic approach (Braun & Clarke, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that our review does not include Indigenous responses to climate change research projects outside of the included countries. While Aotearoa was not the focus of this systematic review, the systematic search found a limited number of studies that examined the specific climate change health impacts on Indigenous or Māori people (Jones et al, 2020). Our intention was to consider the international landscape with regard to including or excluding Indigenous people before engaging in a literature search that was more focused on Māori.…”
Section: Methodology Limitationsmentioning
confidence: 99%
“…Hence, finally, twenty-nine publications remained eligible for inclusion. Out of these 29 articles, five articles were incorporating qualitative research (Bryson et al, 2021 ; Keatts et al, 2021 ; Kowalczewski & Klein, 2018 ; Rautela & Karki, 2015 ; Westoby et al, 2020 ), two articles incorporated Mixed Method Research (Chatwood et al, 2017 ; Durkalec et al, 2015 ); case studies, time series, community-based project and symposium report were one piece each(Amstislavski et al, 2013 ; Galway et al, 2022 ; Huber et al, 2020b ; Rahman & Alam, 2016 ); Seven review articles (1 systematic review, 2 Scoping Review, 4 narrative review) (Ellwanger et al, 2020 ; Galway et al, 2019 ; Jones et al, 2020 ; Lansbury Hall & Crosby, 2022 ; Lebel et al, 2022 ; Schramm et al, 2020 ; Standen et al, 2022 ); 6 commentaries (Hernandez et al, 2022 ; Leal Filho et al, 2021 ; Lewis et al, 2020 ; Redvers et al, 2022 ; Richards et al, 2019 ; Zavaleta-Cortijo et al, 2020 ); 4 perspectives (Callaghan et al, 2020 ; Houde et al, 2022 ; Redvers et al, 2020 ; Timler & Sandy, 2020 ) and 1 editorial was included in the final analysis. (Pollock & Cunsolo, 2019 ) We did not find any meta-analyses, randomized controlled trials, cohort, or case–control studies.…”
Section: Methodsmentioning
confidence: 99%